Fate of the distal aorta following root replacement in Marfan syndrome: a propensity score matched study - Liu, Hao; Chen, Suwei; Luo, Congcong; Zhong, Yongliang; Qiao, Zhiyu; Sun, Lizhong; Zhu, Junming (Frontiers in Cardiovascular Medicine, 2023)
Objective The aortic root is the most frequent segment involved in Marfan syndrome. However, Marfan syndrome is a systemic hereditary connective tissue disorder, and knowledge regarding the outcomes of the native distal aorta after prophylactic aortic root surgery is limited. Methods From April 2010 to December 2020, 226 patients with Marfan syndrome and 1,200 patients without Marfan syndrome who underwent Bentall procedures were included in this study. By propensity score matching, 134 patients were assigned to each group. Clinical manifestations and follow-up data were acquired from hospital records and telephone contact. The cumulative incidence of aortic events was estimated in Marfan and non-Marfan patients with death as a competing risk. Results Patients with and without Marfan syndrome had similar baseline characteristics after propensity score matching. Differences in the aortic root (62.25 ± 11.96 vs. 54.03 ± 13.76, P < .001) and ascending aorta (37.71 ± 9.86 vs. 48.16 ± 16.01, P < .001) remained after matching. No difference was observed in the frequency of aortic adverse events between the two groups (10.5% vs. 4.6%, P = 0.106). The cumulative incidence of aortic events was not different between Marfan and non-Marfan patients (15.03% ± 4.72% vs. 4.18% ± 2.06%, P = 0.147). Multivariate Cox regression indicated no significant impact of Marfan syndrome on distal aortic events (HR: 1.172, 95% CI: 0.263–5.230, P = 0.835). Descending and abdominal aortic diameter above normal at the initial procedure were associated with the risk of distal aortic events (HR: 20.735, P = .003, HR: 22.981, P = .002, respectively). Conclusions New-onset events of the residual aorta in patients undergoing Bentall procedures between the Marfan and non-Marfan groups were not significantly different. Distal aortic diameter above normal at initial surgery was associated with a higher risk of adverse aortic events.